Feasibility of borehole reflection seismology for hard rock mineral exploration - Greenwood, Andrew; Urosevic, Milovan; Pevzner, Roman (SEG, 2010)
Complex geological models typical of hard rock mineral exploration in the Yilgarn Craton of Western Australiahave been created. Through full waveform synthetic modeling, borehole reflection seismology has been tested inthese environments with borehole geometries typical of hard rock exploration techniques. One such example ispresented here. Synthetic testing has shown that borehole reflection seismic sections suffer from lack of aperture in the down-dip direction. Thus Large offsets and higher shot density is required on the down-dip side of the borehole to compensate for this. However at large offsets wavefield identification is complex and correct separation of wavefields for imaging is difficult. These limitations and acquisition specific geometries and processing are discussed here. Initial field studies conducted during a pilot study show potential for seismic imaging from angled boreholes.